Peran Fintech Syariah dalam Mendorong Inklusi Keuangan Berbasis Digital - Ruhliandini, Putri Zafira (Jurnal Dimamu, 2025)
The digital era has positioned Financial Technology (Fintech) as a transformative force in Indonesia's financial ecosystem, offering innovative solutions to overcome traditional banking barriers. This study aims to analyze the strategic role of Bank Syariah Indonesia (BSI) in promoting digital financial inclusion through its Islamic Fintech initiatives, with a focus on the BYOND application. Using a quantitative descriptive method with an explanatory approach, this research collected data through questionnaires distributed to 185 BSI customers selected through purposive sampling from a population of 3.5 million BYOND users. The regression analysis results indicate a positive and significant relationship between Islamic fintech and financial inclusion, with a Pearson correlation coefficient of 0.441 (moderate category). The coefficient of determination (R²) is 0.195, indicating that Islamic fintech contributes 20% to financial inclusion, while the remaining 80% is influenced by other variables. The t-test result (tcount = 2.909 > ttable = 1.65313) confirms the significant effect of Islamic fintech on financial inclusion. This study reinforces the importance of Islamic fintech in enhancing financial inclusion and supporting the Sustainable Development Goals (SDGs).